Regional brain responses in humans during body heating and cooling - Farrell, Michael J. (Temperature (Austin), 2016)
Functional brain imaging of responses to thermal challenge in humans provides a viable method to implicate widespread neuroanatomical regions in the processes of thermoregulation. Thus far, functional neuroimaging techniques have been used infrequently in humans to investigate thermoregulation, although preliminary outcomes have been informative and certainly encourage further forays into this field of enquiry. At this juncture, sustained regional brain activations in response to prolonged changes in body temperature are yet to be definitively characterized, but it would appear that thermoregulatory regions are widely distributed throughout the hemispheres of the human brain. Of those autonomic responses to thermal challenge investigated so far, the loci of associated brainstem responses in human are homologous with other species. However, human imaging studies have also implicated a wide range of forebrain regions in thermal sensations and autonomic responses that extend beyond outcomes reported in other species. There is considerable impetus to continue human functional neuroimaging of thermoregulatory responses because of the unique opportunities presented by the method to survey regions across the whole brain in compliant, conscious participants.